PYROLYSIS OF PALM OIL MILL EFFLUENT (POME) USING MODIFIED LAMPUNG NATURAL ZEOLITE WITH THE SI/AL RATIO OF 1 AS CATALYST - Kamisah Delilawati Pandiangan; Frangky Gom Gom; Nurul Fajriyati; Muhammad Sabil; Tasyadinia Tasyadinia; Hanna Luthfia; Qori Hikmah Faranida; Ilim Ilim; Wasinton Simanjuntak (Jurusan Kimia FMIPA Universitas Lampung, 2024)
In this research, palm oil mill effluent (POME), was pyrolized using a modified Lampung natural zeolite (LNZ) catalyst. Modification was conducted by reducing the Si/Al molar ratio to 1 by mixing certain mass of food grade aluminum food dissolved in 1.0 M NaOH solution and certain mass of LNZ. The mixture was homogenized using a magnetic stirrer, left at room temperature for 12 hours, and finally subjected to hydrothermal crystallization at 100 ºC for 72 hours. The solid sample produced was dried and calcined at 600 °C for 6 hours then characterized using X-ray diffraction (XRD) and Scanning Electron Microscope (SEM) techniques to evaluate the formation of zeolite-A. The BCO produced from the pyrolysis experiment was analyzed using gas chromatography-mass spectrometry (GC-MS), revealing the presence of hydrocarbon as the main components (70%), suggesting the promising potential of the catalyst for further investigation.